Queda em pessoas idosas: um estudo transversal de base populacional - Roscziniak, Taira (2024)
Population aging is a global phenomenon that presents several challenges to public health. Among these challenges, falls in the elderly stand out as one of the main causes of morbidity, mortality and functional decline. Several factors contribute to the risk of falls in the elderly, including physiological changes associated with aging, such as decreased muscle strength, loss of balance and changes in vision. Additionally, external factors such as unsafe home environments and medication use also play a significant role. Therefore, the objective of this dissertation was to identify the prevalence of falls and their associated factors in elderly people living in the city of Coxilha, RS, Brazil. To this end, data from a cross-sectional census-based study conducted in 2021, including all residents aged 60 years or over, were used. The outcome, a fall in the last year, was assessed using the question "Have you had any falls in the last year". The other variables investigated were: age, sex, where they live, marital status, education, handgrip strength and nutritional status. Data collection occurred through a household survey, using a standardized and pre-coded questionnaire. The results indicated that the number of falls was associated with the factors female gender, age 80 years or more, malnutrition/at risk of malnutrition and low handgrip strength. The detailed methodology, results and discussion will be presented in the form of a scientific production, which will later be submitted to a journal in the area.